Switching from Methylphenidate-Immediate Release (MPH-IR) to Methylphenidate-OROS (OROS-MPH): A Multi-center, Open-label Study in Korea - Kim, Bung-Nyun (Korean College of Neuropsychopharmacology, 2011)
OBJECTIVE: The objective of this study was to evaluate the efficacy and safety of methylphenidate HCL OROS extended-release (OROS-MPH) among children with attention deficit hyperactivity disorder (ADHD) who had been previously treated with methylphenidate HCL immediate-release (MPH-IR). METHODS: The sample included 102 children aged 6-12 (9.4±2.6) years who had been diagnosed with ADHD according the criteria of the Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition (DSM-IV; American Psychiatric Association, 1994) and who were attending seven centers in Korea. All participants had been medicated with a stable dose of MPH (10-60 mg/day) for at least 3 weeks before entry into the study. Doses of OROS-MPH were comparable to daily doses of MPH. Efficacy was assessed at baseline (day 0) and at day 28 with the Inattentive-Overactive with Aggression (IOWA) Conners Rating Scale, which was completed by parents/caregivers and teachers, the Peer Interaction Rating Items, which were completed by teachers, and the Clinical Global Impression (CGI) scale, which was completed by child psychiatrists. Paired t-tests were used, and P-values were set at the 0.05 level. RESULTS: Of the subjects, 92.2% were boys and 79.4% were students in the first to fourth grades of elementary school. 72% were diagnosed with the combined type of ADHD, 23% were diagnosed with the inattentive type, and 5% were diagnosed with the hyperactive-impulsive type. The results of the parents' responses to the Inattention/Hyperactivity (I/H) and Oppositional/Defiant (O/D) subscales of the IOWA Conners scale indicated statistically significant improvement in childrens behavior after 4 weeks of treatment with OROS-MPH (t=6.28, p<.001, t=4.12, p<.001). However, the teachers' responses to the Conners I/H and O/D subscales indicated no significant improvement at 4 weeks. The teachers also reported no significant improvements under the OROS-MPH compared with the MPH-IR condition with respect to peer interactions. Scores on the CGI scale showed that 46.1% of children with ADHD were rated by psychiatrists as "minimally improved", 27.5% as "much improved," 1.0% as "very much improved," 3.9% as "minimally worse," and 16.7% as showing "no change". Children exhibited significantly fewer tics with OROS-MPH treatment than with MPH-IR treatment (19.6% vs. 27.7%). We found no differences between in sleep and appetite problems according to medication. CONCLUSION: The results of this study indicated that an MPH-IR regimen can be successfully changed to a once-daily OROS-MPH regimen without any serious adverse effects. The changes in parent/caregiver IOWA Conners ratings suggested that OROS-MPH improved the control of symptoms after school, a finding that is consistent with the 12-h duration of action of this medication. Because the therapeutic effect of OROS-MPH is sufficiently longer than that of a b.i.d. dose of MPH-IR, OROS-MPH had significant positive effects on oppositional/defiant behavior in addition to its effects on the core symptoms of ADHD.